Study of the Influence of Temperature and the Ionic Strength of the Solution on the Adsorption and Conformation of Poly(Acrylic Acid) Macromolecules on the ZrO Surface - M. Wiśniewska (Adsorption Science & Technology)
The influence of temperature and the ionic strength of the solution on the adsorption of poly(acrylic acid) (PAA) and the structure of the corresponding adsorbed layers on a zirconium dioxide surface were studied. All measurements (spectrophotometric, electrokinetic, viscosity and potentiometric titrations) were carried out within the temperature range 15–40°C. The methods used allowed the amount of polymer adsorbed, the surface charge and diffuse layer charge of the ZrO 2 particles in the absence and presence of the polymer, as well as the thickness of the polymer adsorption layers, to be determined. The adsorption measurements demonstrated the occurrence of a minimum in PAA adsorption over the temperature range 25–30°C caused by conformational changes of the polymer macromolecules. In addition, an increase in polymer adsorption and a decrease in the thickness of the polymer adsorption layers were observed as the ionic strength of the solution increased. This was due to the fact that the repulsion interactions between the negatively charged surface and the negatively charged PAA macromolecules were screened by the NaCl used for adjusting the ionic strength. The free energy of PAA adsorption was calculated from the zeta potential data obtained.